Mapeamento da violência motivada por discriminação à identidade de gênero e sexualidade no município de São Paulo: uma metodologia cartográfica na investigação de geografias invisíveis - Vinicius Santos Almeida (Confins)
We present a methodological proposal for the study of physical and verbal violence motivated by discrimination based on gender identity and sexuality, as registered by police reports and occurred in the municipality of São Paulo between 2008 to 2017. The data were collected at the database of the Secretariat of Public Security of the State of São Paulo. We used Analytical and Transformational Cartography (Cauvin; Escobar; Serradj, 2008) to construct anamorphic cartograms in order to visualize the spatial weight of the recorded violence. We then used the anticartogram method (Poncet, 2014) to visualize both the spatial voids and connections between districts. We disaggregated this data and mapped the cases that occurred in public, common and private spaces to further deepen the analysis. Maps were used as fundamental tools to this investigation, allowing the creation of new hypotheses based on methodologies that could go beyond what is immediately aprehensible from the them. The approach and methodology employed, which we call queer cartography, in dialogue with the work of Paul B. Preciado (2017), contribute to an analysis of spatialities and corporealities beyond the limits of Euclidean space, specifically on space, gender and sexuality studies, where maps are seldom present.